Adat Se-Atorang (Local Wisdom) of the Ternate People As a Model of Anti-Corruption Education - Marasabessy, Abd. Chaidir; Utaminingsih, Sri; Pujilestari, Yulita (Cetta: Jurnal Ilmu Pendidikan, 2024)
Although the local government has accommodated the advantages of local values in the Ternate region, educational institutions in the regions have not integrated the advantages of local wisdom values in learning local content. Local wisdom should not be used as a mere symbol, it needs to be integrated in order to create learning that is decorated with wisdom so that the Indonesian generation has strong mental resilience, high morals, forms commendable behavior, and grows an anti-corruption culture. The research aims to describe the customs of the Ternate people as a model of anti-corruption education and its relevance to anti-corruption principles. Descriptive-based qualitative is the choice of this research. Research data is obtained through interviews and supported by relevant documentation and journals and books. Conclusion; 1) "Adat se-Atorang" comes from the ancestral heritage of the Ternate people which is adopted from the basic principle of Islamic teachings (Akhlakulkarimah) which serves as a guide to life, which is practiced continuously to prevent acts of self-destructive greed; 2) "Adat se-Atorang" with values at the core; Galib se-Lakudi (true authority belongs only to God, by His will, man only carries out His entrustment; Sere se-Duniru (in the construction of social interaction relationships, human beings must not deviate from His rules); Cing se-Cingari (when acting, it must be seen by the public, always aware of itself that there is supervision of man and God); Cara se-Ngale (doing a work always refers to the guidance of God (Allah Swt); Bobaso se-Rasai (the gift of God's knowledge to humans to maintain behavior in social relationships; Loa se-Bannari (if trust is given, it must be done honestly, correctly and straightly); Duka se-Cinta (grow an attitude of caring and tolerance for others); Baso se-Hormati (respect others and do not accuse or blame others). The value in question has a universal meaning and is in line with the principles of anti-corruption and the spirit of the mandate of the Anti-Corruption Law.